2010
DOI: 10.1002/srin.201000086
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Phosphorus and Sulphur Removal during Basic Oxygen Steelmaking

Abstract: Removal of impurity elements from hot metal is essential in basic oxygen steelmaking. Oxidation of phosphorus from hot metal has been studied by several authors since the early days of steelmaking. Influence of different parameters on the distribution of phosphorus, seen during the recent work of the authors, differs somewhat from that reported earlier. On the other hand, removal of sulphur during steelmaking has drawn much less attention. This may be due to the magnitude of desulphurisation in oxygen steelmak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Approximately 70 pct of the steel produced worldwide is through the integrated BF-BOF route, [50] making the BOF, which seems like a simple converter furnace on the surface, a critical technology to the existence of steel in its plethora of uses today. The understanding of the BOF has undergone continual development, and with regard to the pathway of refining, there are two key contrasting models in existence: (1) The understanding that the exceedingly high temperatures in the ''hot zone'' (the impingements area of the oxygen gas jet) cause reactions to occur in this area at such a high rate the contribution of this zone is vastly significant; [21,[51][52][53] (2) the gas/slag/metal emulsion is the most significant contributor to the reaction processes in the BOF due the cumulative vast interfacial area between slag and metal, which is generated and held here due to the high number of droplets and overall volume of the emulsion. [52,[54][55][56][57][58][59][60][61] The hot-zone-controlled model works on the principle of elevated temperatures in the hot zone of the BOF (the area directly under the nozzle of the oxygen lance).…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
“…Approximately 70 pct of the steel produced worldwide is through the integrated BF-BOF route, [50] making the BOF, which seems like a simple converter furnace on the surface, a critical technology to the existence of steel in its plethora of uses today. The understanding of the BOF has undergone continual development, and with regard to the pathway of refining, there are two key contrasting models in existence: (1) The understanding that the exceedingly high temperatures in the ''hot zone'' (the impingements area of the oxygen gas jet) cause reactions to occur in this area at such a high rate the contribution of this zone is vastly significant; [21,[51][52][53] (2) the gas/slag/metal emulsion is the most significant contributor to the reaction processes in the BOF due the cumulative vast interfacial area between slag and metal, which is generated and held here due to the high number of droplets and overall volume of the emulsion. [52,[54][55][56][57][58][59][60][61] The hot-zone-controlled model works on the principle of elevated temperatures in the hot zone of the BOF (the area directly under the nozzle of the oxygen lance).…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
“…Therefore, Young et al modified the Sosinsky's expression and suggested the following relationships: For Λ ≤ 0. [32,47,48,54] two types of experiments can be performed to obtain the sulphide capacity of a slag under equilibrium conditions. The first technique [32,54] involves equilibrating slag and metal in a controlled atmosphere.…”
Section: Relationship Between Optical Basicity and Sulphide Capacitymentioning
confidence: 99%
“…[32,47,48,54] two types of experiments can be performed to obtain the sulphide capacity of a slag under equilibrium conditions. The first technique [32,54] involves equilibrating slag and metal in a controlled atmosphere. Then sulphide capacity can be calculated from the sulphur distribution ratio, temperature, and the oxygen potential of the system according to Equation 2-37.…”
Section: Relationship Between Optical Basicity and Sulphide Capacitymentioning
confidence: 99%
“…The strength of steel is detrimental to the sulfur content of iron ore and pig iron (from which steel is made); therefore, excess steel sulfur content influences the quality of steel products. It has been reported that sulfur causes failure of steel put in service in the very hot environment and also enhances the rate of corrosion of steel structures and affects the reduction behavior of iron burden material . The allowable sulfur content of raw materials for steel production depends on the application of the produced steel.…”
Section: Introductionmentioning
confidence: 99%